Occurrence of vancomycin-resistant enterococci in relation to the administration of glycopeptide antibiotics - Kolár, M; Vágnerová, I; Látal, T; Kohnová, I (Acta Universitatis Palackianae Olomucensis Facultatis Medicae, 1999)
Occurrence of vancomycin-resistant enterococci and its relationship to the administration of glycopeptide antibiotics (vancomycin, teicoplanin) was described. A total number of 628 strains of the genus Enterococcus was isolated in the Hemato-oncologic Department of the University Hospital in Olomouc in 1997. Seven strains (1.1%) were found to be resistant to vancomycin. Five of them were identified as Enterococcus faecalis of phenotype VanB, and two strains as E. faecium of phenotype VanA. The administration of vancomycin and teicoplanin in the Hemato-oncologic Department amounted to 85.7% and 89.2%, respectively, of the total consumption of these drugs at the University Hospital.
Keywords: Enterococcus faecalis; vankomycin; Teicoplanin; Vancomycin; Enterococcus; lidé; Microbial Sensitivity Tests; Vancomycin Resistance; mikrobiální testy citlivosti; antibakteriální látky; Anti-Bacterial Agents; teikoplanin; rezistence na vankomycin; Enterococcus faecium; Humans